Hydrolytic Conversion of Sawdust as a Step of Complex Wood Waste Processing - Antonina Stepacheva; Yury Lugovoy; Mariia E. Markova; Oleg V. Manaenkov; Valentina G. Matveeva; Mikhail Sulman (Chemical Engineering Transactions)
Biomass can be considered as a potential resource for the production of renewable fuels. Lignocellulose biomass is a widely available, renewable, biodegradable, and biocompatible resource that can potentially reduce the dependence of modern society on fossil resources. It is a potential feedstock for the production of heat, electricity, fuel, chemicals, and other bioderived products. Considerable attention of researchers is directed to the conversion of biomass into bioenergy through chemical, biochemical, or thermochemical processes. Hydrolysis is considered to be one of the important steps to convert biomass into valuable chemicals. During hydrolysis, liquid rich in sugars with a certain amount of dissolved lignin, usually called hydrolysate, is formed. In this paper, the influence of the catalyst type, temperature, catalyst concentration, and solvent type on the conversion and composition of hydrolysate was studied. The highest yield of hydrolysis products (hexoses and pentoses) reached up to 80 wt. % at a temperature of 220 °C in water medium in the presence of 1.5 wt. % of sulfuric acid.